Diagnostic Assessment Reviews: is cost-effectiveness analysis helpful or necessary?. Issue 4 (October 2018) - Mistry, Hema; Mason, James
Objective: Diagnostic Assessment Reviews are part of the work programme of the National Institute of Health and Care Excellence (NICE) in England to evaluate emergent medical technologies and so ensure timely and consistent adoption within the National Health Service (NHS). New diagnostics have the potential to improve health outcomes and impact positively on health service resource use. This study sought to assess the quality of economic evidence informing Diagnostic Assessment Reviews. Methods: We reviewed 27 Diagnostic Assessment Reviews that had been published by NICE as of 30 May 2017 by summarizing and interpreting the evidence that was used to carry out cost-effectiveness analyses. Common issues and challenges of the assessment process were illustrated. Findings: DARs differed in the methods and assumptions used to construct economic models, and linkage of economic model and diagnostic findings. Even though some diagnostic technologies were estimated to be cost-effective, they were not always adopted for routine use in the NHS. The majority of Diagnostic Assessment Review economic models relied heavily on assumptions and expert opinion, with considerable uncertainty about the cost-effectiveness of diagnostic testing. Conclusions: Diagnostic Assessment Reviews appraisals as commissioned by NICE typically feature varying evidence for diagnostic performance and limited evidence for resource implications and quality of life, often leading to recommendations for further research. Given the process opportunity cost, a two-stage topic selection process, with initial assessment specifying further research and proceeding to full assessment when adequate evidence is available may be more appropriate and help signal to diagnostics companies the type of research evidence required.